Effects of the social security reform in colombia on equity to access and use of health services (2000)
In order to evaluate the effects of the new health system upon the equity to access and use of the health services, two cross sections of the population were compared: before Law 100 of 1993, which created the General System for Social Security in Health-SGSSS-, and after the law was passed. The changes in the distribution of an indicator of equity in access to health care services, the affiliation to the General System for Social Security in Health, were assessed. Additionally, two groups were compared in the 1997 cross section, affiliated and non-affiliated to the SGSSS, in order to assess the changes in the equity of use of hospital services and health care services in general. The results obtained show that between 1993 and 1997 the coverage of the SGSSS increased from 23% to 57%. This increase in coverage was more dramatic amongst the poorest sectors of the population: in the homes of people in the lowest tenth percentile of income the coverage increased from 3.1% to 43.7%, and the index of concentration of affiliation to the SGSSS decreased by half: from 0.34 to 0.17. By contrast, the indicators of concentration corresponding to the use of health services varied very little even after the adjustments by age, gender and needs. These results suggest a positive impact of the SGSSS on the inequities of access to health services, but the effects upon the inequities of use of health services are not clear.